EFFECT OF CULTURAL OF FAMILY, CONFLICT MANAGEMENT, AND TOLERANCE INTER-RELIGIOUS HARMONY STABILITY OF PEOPLE IN BATAM - I Wayan Catra Yasa; Makruf Akbar; Muchlis Lauluddin (Program Pascasarjana Universitas Negeri Jakarta, 2019)
The purpose of this study was to determine the influence of family culture, conflict management, tolerance and inter-religious harmony to the stability of people's lives. This study uses survey (survey research), the research aims to identify and determine the position of instantaneous variables (status quo variable) based on the data available at the time, and the relationship between the variables studied. The population in this study are all people of the city of Batam, while While the research targets are religious leaders who are members of Harmony Faith Dialog Forum (FKUB) in Batam that at the time of the study the total number is 300 people and the sample have as many as 172 people , The results showed that the stability of people's lives are directly affected family culture, conflict management, and inter-religious harmony. The study also found inter-religious harmony is directly affected family culture, conflict management, and tolerance. The study also found that tolerance is directly influenced by family culture and conflict management. Based on these findings it can be concluded that any changes or variations that occur in the family culture, conflict management, and inter-religious harmony results in the increase in the stability of people's lives. Therefore, the stability of people's lives, family culture, conflict management, and inter-religious harmony can be used as guidelines in making strategic planning to the stability of people's lives.